RECONSTRUCTION OF VALUE EDUCATION IN ISLAMIC ELEMENTARY SCHOOL (A CRITICAL ANALYSIS IN CONTEMPORARY EDUCATION) - Ahmad Shofiyuddin Ichsan (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This study aimed to find out the importance of value education to be reconstructed in Elementary School in the contemporary education. This study was a library research with descriptive exploratory based on the results of reflective evaluations from the relevant sources and reinforced by field studies from researcher directly. The study results revealed that the increasingly widespread the mischief of Elementary School students provided an open space to reconstruct the value education. So, it was necessary to take steps in implementing value education including the program routine of "moral guidances", strengthening tolerance in the school environment, providing good examples by the teachers, and building a culture of "inclusive schools". While to reconstruct value education as a solution which could be done through: 1) mapping schools where were prone to mischief, 2) synergizing between schools, academics, community leaders, and police, 3) comprehensively integrating the science across all subjects, 4) adopting a system of pesantren education, 5) organizing and ensuring the school programs in the short, medium, and long terms, 6) synergizing two educational institutions (school and madrasah diniyah), and 7) implementing the power of prayer from the teachers in their every ritual.